Computed Tomography-Based Interstitial Brachytherapy for Recurrent Cervical Carcinoma in the Vaginal Apex. Issue 1 (January 2022) - Engineer, R.; Chopra, S.; Shukla, R.; Mahantshetty, U.; Phurailatpam, R.; Ghadi, Y.; Gupta, S.; Shrivastava, S.K.
Abstract: Aims: To determine the factors influencing the outcomes of patients with recurrences post-hysterectomy for cervical cancers treated with external beam radiotherapy (EBRT) and interstitial brachytherapy. Materials and methods: This prospective study accrued 90 patients between October 2008 and May 2014. All patients had had a prior hysterectomy and were diagnosed with recurrent vaginal apex cancers with squamous cell carcinomas. All underwent EBRT of 50 Gy (2 Gy/fraction) using tomotherapy-based image-guided intensity-modulated radiotherapy with concurrent chemotherapy of weekly cisplatin (40 mg/m 2 ) followed by high dose rate interstitial brachytherapy boost of 20 Gy (4 Gy/fraction twice a day). Local relapse, disease-free and overall survival were determined. Results: At a median follow-up of 74 months (4–123 months), 10/90 (11%) patients had local failure as the first site of relapse and 12/90 (13.3%) had first distant relapse. Only one patient had synchronous local and distant relapse. The 7-year local relapse-free, disease-free and overall survival were 87.6, 68.3 and 68.3%, respectively. Grade 2 and 3 rectal toxicity were seen in 5.6 and 3.1% of patients, respectively. Among these, two (2.2%) patients underwent temporary diversion colostomy due to vaginal sigmoid and rectovaginal fistula. Grade 2 and 3 bladder toxicity were seen in 5.6 and 1.1% of patients, respectively. In summary, the lateral disease extent ( P = 0.048) and the presence of nodal disease at diagnosis ( P = 0.08) had a statistically significant or borderline impact on local relapse without any impact on disease-free survival. Tumour size in itself did not affect overall survival. Conclusion: With the integration of EBRT and interstitial brachytherapy, most vaginal apex recurrences can be salvaged. An excellent local control and survival is achievable using intensity-modulated radiotherapy with image guidance and concurrent chemotherapy followed by high dose rate interstitial brachytherapy. Highlights: We studied outcomes in patients with vaginal recurrences after surgery. The study used IG-IMRT to reduce dose to organs at risk and escalate nodal dose. Interstitial brachytherapy using perineal template to a dose of 20 Gy/5 fractions. 7-year local relapse-free, disease-free and overall survival were 87.6, 68 and 68%, respectively. Grade 3 rectal and bladder toxicity were seen in 3.1 and 1.1% of patients, respectively.